An Experimental Study on Strength and Self-Healing Characteristics of Bacterial Concrete (International Journal of Innovative Research in Engineering & Management, 2024)
In modern era, concrete is widely used in  building material. Concrete is durable, strong and locally  available. It has a property of resisting the compressive  load to a limit but if the load applied goes beyond the  limit, the strength of concrete is reduced because of the  development of the cracks in the concrete. Thus the treatment for these cracks becomes very  expensive. The development of cracks in concrete affects  the serviceability limit of concrete. The influx of  water and harmful chemicals into the concrete may  decrease both the strength and life. Structural failure  may be caused by micro-cracks. One way to avoid  costly manual maintenance and repair is to include  an autonomies self-healing mechanism in concrete.  One such an alternative mechanism is correctly being  studied i.e. a novel technique based on the  application of bio-mineralization of bacteria in  concrete. The applicability of specifically calcite  mineral precipitating bacteria for concrete repair and  plugging of pores and cracks in concrete has been  investigated and studies on the possibility of using  specific bacteria as a sustainable and concrete  embedded self-healing agent was studied and results  from ongoing studies are discussed. Synthetic  polymers such as epoxy treatment etc. are now a days  used for repair of concrete are harmful to the  environment, hence the biological repair technique is  focused. Recently, it has been found that microbial carbonate  Precipitation resulting from the metabolic activities of  micro-organisms in concrete modified the overall  behavior of concrete. Hence, in this paper, we explain  the bacterial concrete, its classification and types of  bacteria, chemical processes to fix the micro cracks,  advantages ,disadvantages and the possibilities on  application of micro-organisms in the concrete. The  different strengths of normal concrete and concrete  with bacillus were analyzed and the tests were  conducted and compared.
Keywords: Bacteria Bacillus Subtillus; Concrete; Aggregates; Cement; Strength